Attitudes towards Gender Roles and Perception of Gender (in)Equality in Croatia - Kamenov, Željka (Array, 2010)
The aim of this study was to ascertain the role of egalitarian and traditional attitudes toward gender roles in the way people perceive the problem of gender inequality in Croatia. Theoretically, we would expect that people with more egalitarian attitudes perceive more inequality than people with traditional attitudes. However, since people have different life experiences, we would expect that situational differences (e. g. living in a rural vs. urban area) also play a significant role in this perception. A comprehensive questionnaire was administered to a national, representative sample of 1363 Croatian citizens aged 15 to 89, stratified according to town size and region, and controlling for gender, age and education level. We administered the Attitudes toward gender roles scale, and assessed the perception of gender (in)equality and awareness of gender discrimination. Not only were we interested in the overall level of gender discrimination, but we also wanted to know about gender discrimination in different areas – family life, education, work life and politics. We discuss the role of attitudes and situational variables in explaining the differences in perception and sensitivity to gender inequality. Results are discussed separately for men and women, since women see gender discrimination as a much bigger problem than men do. Some interesting patterns of results in particular areas of life (family, education, work and politics) are also elaborated.